2002
DOI: 10.1063/1.1483299
|View full text |Cite
|
Sign up to set email alerts
|

Polymer induced depletion potentials in polymer-colloid mixtures

Abstract: The depletion interactions between two colloidal plates or between two colloidal spheres, induced by interacting polymers in a good solvent, are calculated theoretically and by computer simulations. A simple analytical theory is shown to be quantitatively accurate for case of two plates. A related depletion potential is derived for two spheres; it also agrees very well with direct computer simulations. Theories based on ideal polymers show important deviations with increasing polymer concentration: They overes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(159 citation statements)
references
References 80 publications
6
151
2
Order By: Relevance
“…The comparison between our results and the experiments of Aarts et al 21 is quantitatively better than the results of the AOV model, although de Hoog and Lekkerkerker 12 show that it is difficult to obtain accurate interfacial tension measurements. In addition, we compare our results with the predictions of the extended free volume theory plus a square gradient approximation to evaluate the tension 45 and the DFT of Moncho-Jorda et al 47 The DFT uses effective one-component pair potentials between the colloids that include the excluded volume interaction according to the approach of Louis et al 46 The predictions of the two theories are very close to each other and to our simulation results. Figure 7 shows the phase diagram of colloid-polymer mixtures confined between two hard walls with separation distances H / c = ϱ ,16,8,4,2.…”
Section: A Bulk Phase Behavior and Gas-liquid Interfacial Tensionsupporting
confidence: 65%
“…The comparison between our results and the experiments of Aarts et al 21 is quantitatively better than the results of the AOV model, although de Hoog and Lekkerkerker 12 show that it is difficult to obtain accurate interfacial tension measurements. In addition, we compare our results with the predictions of the extended free volume theory plus a square gradient approximation to evaluate the tension 45 and the DFT of Moncho-Jorda et al 47 The DFT uses effective one-component pair potentials between the colloids that include the excluded volume interaction according to the approach of Louis et al 46 The predictions of the two theories are very close to each other and to our simulation results. Figure 7 shows the phase diagram of colloid-polymer mixtures confined between two hard walls with separation distances H / c = ϱ ,16,8,4,2.…”
Section: A Bulk Phase Behavior and Gas-liquid Interfacial Tensionsupporting
confidence: 65%
“…In recent years, there have been significant theoretical developments which take into account the polymeric excluded-volume interactions [30][31][32][33][34][35][36][37][38][39][40][41]. As examples of methods that enable the prediction of the phase behavior of colloid-polymer mixtures we mention polymer-colloid liquid state theory [31][32][33][34], thermodynamic perturbation theories [12,35], density functional theory [36,37], a Gaussian-core model [14,38,39], and computer simulations of HS plus self-avoiding polymer chains [40,41].…”
Section: General Backgroundmentioning
confidence: 99%
“…As examples of methods that enable the prediction of the phase behavior of colloid-polymer mixtures we mention polymer-colloid liquid state theory [31][32][33][34], thermodynamic perturbation theories [12,35], density functional theory [36,37], a Gaussian-core model [14,38,39], and computer simulations of HS plus self-avoiding polymer chains [40,41]. To obtain phase lines these methods require a significant amount of numerical work.…”
Section: General Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Both groups have adopted different approaches. To obtain the interaction potential between two colloidal spheres mediated by excluded volume polymers Aarts et al [27] have used the generalized Gibbs adsorption equation approach [30], whereas Moncho-Jorda et al [28] have used a depletion potential obtained from direct computer simulations [31]. Both groups have found that the interfacial tension is lower for interacting polymers than for the AOV model.…”
Section: Introductionmentioning
confidence: 99%